Decreased circulating omega-3 fatty acids increase the risk of myocardial infarction: a two-sample Mendelian randomization study - Wang, Wei; Yang, Linfei; Zhang, Jing; Xiang, Haiyun (Frontiers in Cardiovascular Medicine, 2024)
Background: Many studies have shown that omega-3 fatty acids may play critical roles in cardiovascular diseases. Myocardial infarction(MI) typically results from a thrombotic occlusion of a coronary artery leading to myocardial ischemia. Thus, this study aim to examine the association between omega-3 fatty acids and MI. Methods: A two-sample mendelian randomization study was used to explore the causal relationship between circulating omega-3 fatty acids and the risk of MI performed by MR-Egger regression, inverse-variance weighted (IVW), weighted median and weighted mode. Results: Five single nucleotide polymorphisms (SNPs) strongly related to circulating omega-3 fatty acids were selected as instrumental variables from a published GWAS meta-analysis including 13544 subjects. We extracted summary data for the risk of MI from another GWAS meta-analysis including 171876 individuals (43676 cases and 128199 controls). The genetically predicted lower circulating omega-3 increased the risk of myocardial infarction showed by the results of IVW (OR = 1.224, 95%CI = 1.045-1.433, P = 0.012), weighted median method (OR = 1.171, 95%CI = 1.042-1.315, P = 0.008) and weighted mode (OR = 1.149, 95%CI = 1.002-1.317, P = 0.117), although the result of MR Egger was not significant (OR = 0.950, 95%CI = 0.513-1.760, P = 0.880) with a wider confidence interval. Conclusion: The findings from our mendelian randomization analysis suggest that the association between omega-3 fatty acid levels and MI is likely causal..